Improving Student Learning Outcomes in Islamic Religious Education (PAI) Learning Through Problem-Based Learning (PBL) Model in Class IV Public Elementary School 05 Lubuk Gadang in The 2024/2025 Academic Year - Yetti Wilda (BiCED Proceeding, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education using the Problem-Based Learning (PBL) model in grade IV students at SDN 05 Lubuk Gadang. The research was conducted in two cycles, with cycle II as a follow-up to cycle I. The results of cycle II showed a significant improvement in student activity, including involvement, understanding of the material, and response to learning media. However, the learning completeness in cycle II only reached 70%, indicating the need for a subsequent cycle to achieve 100% completeness. The study concludes that the PBL model can enhance learning outcomes, but further improvements are necessary to ensure optimal success in the learning process.